2020
DOI: 10.1177/2151459320976533
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the Inpatient Cost of Care in the Treatment of Isolated Geriatric Intertrochanteric Hip Fractures

Abstract: Introduction: Geriatric hip fractures are a major, costly public health issue, expected to increase in incidence and expense with the aging population. As healthcare transitions towards value-based care, understanding cost drivers of hip fracture treatment will be necessary to perform adequate risk adjustment. Historically, cost has been variable and difficult to determine. This study was purposed to identify variables that can predict the overall cost of care for geriatric intertrochanteric (IT) hip fractures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…12 - 14 Although the National Readmissions Database does not record a total cost for a patient care episode in its entirety, these variables serve as a proxy for estimating increased cost to the care facility. It has previously been shown that length of stay is a strong correlative measure for inpatient cost care (R 2 = .77) 1 supporting our hypothesis of variance in cost within this bundle.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…12 - 14 Although the National Readmissions Database does not record a total cost for a patient care episode in its entirety, these variables serve as a proxy for estimating increased cost to the care facility. It has previously been shown that length of stay is a strong correlative measure for inpatient cost care (R 2 = .77) 1 supporting our hypothesis of variance in cost within this bundle.…”
Section: Discussionsupporting
confidence: 86%
“…While this study is focused on the potential financial discrepancies between services provided and reimbursement, the National Readmission Database that was used for this dataset does not measure the true total cost of a bundle of care. Other data elements that have been shown to be accurate surrogates for cost such as readmission rate 8 and length of stay (R 2 = .77), 1 , 23 as well as others such as comorbidities and chronic diagnoses, were used to approximate expenses and the variety of costs when stratified with different approaches. Although the NRD lacks data from the post-acute perspective such as outpatient, home care, and skilled nursing facilities, this study focused on the hospital cost and readmission numbers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With an expected longevity of up to 20 years, a flooring intervention presents the opportunity for a significant return on investment [17][18][19][20]. If proven effective at preventing hip fractures for example (which have been estimated to incur upwards of USD 6500 per fracture to various international health systems, often considerably more [21][22][23]), the cost of purchasing and installing a new floor could be quickly recouped. Yet rarely do interventions come without risk, and for shock-absorbing flooring interventions the concerns are twofold: 1) the debated potential for a softer surface to inadvertently increase the risk of falling for those already unsteady on their feet [24][25][26][27][28][29][30][31][32][33][34][35]; and 2) the risk to staff who may find manoeuvring wheeled equipment (such as beds and trolleys) harder, due to greater resistance to pushing and pulling forces [36][37][38][39], potentially increasing the risk of musculoskeletal injuries [40,41].…”
mentioning
confidence: 99%